PHRASEOLOGICAL SYNONYMIC SERIES STUDY IN ENGLISH AND UZBEK - Atadjanova, Sevara (Журнал иностранных языков и лингвистики, 2023)
In our article, we will get information about the figurative, stylistic coloring of phraseological synonyms in English and Uzbek.